The Developmental Switch in Bacteriophage λ: A Critical Role of the Cro Protein. Issue 1 (5th January 2018) - Lee, Sangmi; Lewis, Dale E.A.; Adhya, Sankar
Abstract: Bacteriophage λ of Escherichia coli has two alternative life cycles after infection–host survival with lysogen formation, or host lysis and phage production. In a lysogen, CI represses the two lytic promoters, pR and pL, and activates its own transcription from the auto-regulated pRM promoter. During induction from the lysogenic to lytic state, CI is inactivated, and the two lytic promoters are de-repressed allowing for expression of Cro from pR. Cro is known to repress transcription of CI from pRM to prevent lysogeny. We show here that when Cro and CI are both present but at low levels, the low level of Cro initially stimulates the lytic promoters while CI repressor is still present, stimulating the level of Cro to a concentration required for pRM repression. Cro has no stimulatory effect without the presence of CI. We propose that this early auto-activating role of Cro at lower concentrations is essential in the developmental switch to lytic growth, whereas pRM repression by Cro at relatively higher concentrations avoids restoring lysogeny. Graphical Abstract: Highlights: Bacteriophage λ Genetic Switch revisited Prophage induction